Publish Or Perish Training For Non-PNS Islamic Religious Counsellors In Sambas Regency - Rifqi Muhammad; Yusrain Yusrain; Manja Manja; Enik Sartika; Yasti Yasti (Fakultas Teknik Universitas Cenderawasih, 2023)
The purpose of this paper is to report court activities in the form of PoP training activities for Non-PNS Islamic Religious Counsellors in Sambas Regency. The service report method uses descriptive qualitative with three stages, namely planning, implementation and evaluation. The results of community service activities show that Non-PNS Islamic Religious Counsellors improve their ability to find empirical data, this ability certainly has an impact on the ease of making papers as coursework. This is evidenced by the results of the pretest and posttest showing an increase in ability, with an increase of around 21 percent